Recovery of Reusable Water from Sulphate-Rich Industrial Effluents - Motaung, S; Maree, J; Bologo, L; de Beer, M; Radebe, V (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
The removal of acid, metals and sulphate from mine water (gold mines) was assessed using the integrated limestone/sulphide/lime/BaCO3 process. The laboratory scale integrated process was used for neutralization and removal of the total dissolved solids content, from 7600 to 400 mg/l. Metals such as Ni, Co, Fe(II) and Mn were removed effectively through precipitation with CaS or Ca(HS)2. The rate of sulphate removal during gypsum crystallization was influenced by the gypsum seed crystal content. The rate of sulphate removal during BaCO3 treatment was influenced by pH, CaCO3 solids and BaCO3 solid concentration. Ca(HS)2 was produced from CaS bypassing CO2 through a CaS slurry. Further CO2 additions resulted in H2S-stripping. This process is seen to be an effective way of solving an environmental problem associated with acid mine drainage (AMD).